Guided evaluation and standardisation of mesenchymal stem cell culture conditions to generate conditioned medium favourable to cardiac c-kit cell growth - Ng, Wai Hoe; Umar Fuaad, Mimi Zulaikha; Azmi, Siti Maisura; Leon, Yin Yee; Yong, Yoke Keong; Ng, Angela Min Hwei; Tan, Jun Jie (Springer, 2019)
Mesenchymal stem cells (MSCs) are known to secrete cardioprotective paracrine factors that can potentially activate endogenous cardiac c-kit cells (CCs). This study aims to optimise MSC growth conditions and medium formulation for generating the conditioned medium (CdM) to facilitate CC growth and expansion in vitro. The quality of MSC-CdM after optimisation of seeding density during MSC stabilisation and medium formulation used during MSC stimulation including glucose, ascorbic acid, serum and oxygen levels and the effects of treatment concentration and repeated CdM harvesting were assessed based on CC viability in vitro under growth factor- and serum-deprived condition. Our data showed that functional CdM can be produced from MSCs with a density of 20,000 cells/cm2, which were stimulated using high glucose (25 mM), ascorbic acid supplemented, serum-free medium under normoxic condition. The generated CdM, when applied to growth factor- and serum-deprived medium at 1:1 ratio, improved CC viability, migration and proliferation in vitro. Such an effect could further be augmented by generating CdM concentrates without compromising CC gene and protein expressions, while retaining its capability to undergo differentiation to form endothelial, smooth muscle and cardiomyocytes. Nevertheless, CdM could not be repeatedly harvested from the same MSC culture, as the protein content and its effect on CC viability deteriorated after the first harvest. In conclusion, this study provides a proof-of-concept strategy to standardise the production of CdM from MSCs based on rapid, stepwise assessment of CC viability, thus enabling production of CdM favourable to CC growth for in vitro or clinical applications.